Pelatihan 3D Modelling Menggunakan Blender Pada SMA Methodist-8 Medan: Richard Parlindungan Simanjuntak, Ilham Safar, Dewi Wahyuni - Safar, Ilham; Simanjuntak, Richard Parlindungan; Wahyuni, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Training in the field of 3D Modeling using Blender has been completed for students at Methodist-8 Medan High School (SMA). The aim of this training is to provide basic understanding and skills in creating and designing animated 3D objects that can be expressed in real visual form, both in terms of shape, texture and size of the object using the Blender design tool. This training method includes several practical stages focusing on the introduction of Blender 3D, basic concepts of 3D animation, design, 3D measurements, framework and modeling, texturing and visualization. The students were given a step-by-step 3D Modeling learning guide and were guided directly on how to create and design animated 3D objects until completion by forming group teams to hone their skills in improving their creativity and understanding of the art of design that is responsive and has aesthetic value. The results of this training showed a 90% increase in students' understanding in learning the basic concepts of 3D animation with practical design tools using Blender. They were able to produce simple 3D modeling designs with good animated 3D objects, appropriate textures so that the resulting objects looked real, then implemented the results of their designs in the form of animating character visualizations and 100% response from the students requested that this training be continued in the activity session next period of community service.